2019
DOI: 10.1177/2332858419850792
|View full text |Cite
|
Sign up to set email alerts
|

Toward a More Complete Understanding of Writing Enjoyment: A Mixed Methods Study of Elementary Students

Abstract: This mixed methods study explored elementary students' (N = 263) writing enjoyment, their perceptions of teacher writing enjoyment, self-regulation, and grades. In the quantitative strand, we examined how student perceptions of teacher writing enjoyment and student writing enjoyment relate to student writing self-regulation and writing grades using structural equation modeling. Findings revealed a positive relationship among student-perceived teacher writing enjoyment, student writing enjoyment, and student wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
3
11
1
2
Order By: Relevance
“…In contrast, if the teacher acts reluctantly, learners' motivation will be dampened and the levels of their writing enjoyment and writing vocabulary strategy will also be reduced. This is consistent with the study of Zumbrunn et al (2019), in which they found the social aspects of writing could foster writing enjoyment. This is, in fact, the emotional transmission (Frenzel et al, 2018;Han et al, 2022).…”
Section: (B) Correlation Analysis Between Wvs and Flwesupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, if the teacher acts reluctantly, learners' motivation will be dampened and the levels of their writing enjoyment and writing vocabulary strategy will also be reduced. This is consistent with the study of Zumbrunn et al (2019), in which they found the social aspects of writing could foster writing enjoyment. This is, in fact, the emotional transmission (Frenzel et al, 2018;Han et al, 2022).…”
Section: (B) Correlation Analysis Between Wvs and Flwesupporting
confidence: 91%
“…There are already abundant studies on learners' overall foreign language enjoyment, but few are about the domain-specific foreign language enjoyment, especially the enjoyment of writing. Zumbrunn et al (2019) focused on the relationship between writing enjoyment, their perceptions of teacher writing enjoyment, self-regulation, and grades, and they found positive relationships among those elements. Zhang and Dong (2022) conducted a study about the relationship between motivational-regulation strategies and proximal/distal second-language writing achievement emotions.…”
Section: B Foreign Language Enjoyment (Fle) and Foreign Language Writ...mentioning
confidence: 99%
“…Our findings suggest that efficacious beliefs are better modeled by an ESEM. Whereas findings across recent writing self-efficacy literature show that efficacious beliefs exhibit latent factor correlations and suggest conceptual overlap (e.g., Bruning et al, 2013;Limpo and Alves, 2017;Ramos-Villagrasa et al, 2018;Zumbrunn et al, 2020Zumbrunn et al, , 2021DeBusk-Lane et al, 2021), the present study provides statistical evidence that such correlations are, in some part, better modeled across all items. Although this is common in the social sciences, especially in psychological measures (see Morin et al, 2016c), it does indicate that there is shared variability across latent factors and, given new statistical approaches (e.g., ESEM), may better be modeled to represent reality more closely.…”
Section: Rq1: Conceptual Overlap Of Writing Self-efficacy Dimensionscontrasting
confidence: 77%
“…Further, recent empirical evidence brings into question whether the adapted SEWS is best modeled by three distinct factors (Zumbrunn et al, 2020(Zumbrunn et al, , 2021DeBusk-Lane et al, 2021) or a single factor alone (Ekholm et al, 2015;Zumbrunn et al, 2016). Across both the original 16-and the adapted 9-item measures, moderate latent factor correlations, large first factor eigenvalues, and moderate correlations among the specific latent factors to other unidimensional writing self-efficacy measures suggest the presence of a hierarchical or global factor (e.g., Reise et al, 2013;MacArthur et al, 2015;Ramos-Villagrasa et al, 2018;Zumbrunn et al, 2020Zumbrunn et al, , 2021DeBusk-Lane et al, 2021).…”
Section: Aligning a Measurement Model With Theorymentioning
confidence: 99%
“…Within the domain of skills-specific enjoyment, Wang and MacIntyre’s (2021) study indicated that FL listening enjoyment facilitated the use of listening strategies and reduced listening difficulties. Similarly, Tahmouresi and Papi (2021) found that FL writing enjoyment significantly positively predicted FL writing motivation, a variable underlying FL writing achievement, echoing other findings of the importance of writing enjoyment for first language writing performance (Collie et al, 2016; Zumbrunn et al, 2019).…”
Section: Introductionsupporting
confidence: 63%